1982
DOI: 10.1113/jphysiol.1982.sp014379
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intracochlear and systemic furosemide on the properties of single cochlear nerve fibres in the cat

Abstract: SUMMARY1. Tuning properties and spontaneous discharge rate of single cochlear fibres in the anaesthetized cat were determined during short-and long-term poisoning of the cochlea by locally and systemically applied furosemide.2. With intra-arterial administration offurosemide, short-term reversible elevation occurred of the low threshold sharply tuned 'tip' segment of the frequency threshold ('tuning') curve (f.t.c.) by up to 40 db, without substantial changes in the threshold of the low frequency 'tail' segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…An ABR threshold elevation between 25 and 50 dB is apparently due to the reduction of the EP (from ~85 mV in WT mice to ~18 mV in heterozygous mice). This is consistent with the level of furosemide-induced reduction of the basilar membrane vibration [12] and threshold elevations in the tuning curves of auditory nerve fibers [13,14]. In homozygous mice, concurrent absence of intermediate cells and the EP further confirms the role of the intermediate cells in generating the EP [2,5,8].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An ABR threshold elevation between 25 and 50 dB is apparently due to the reduction of the EP (from ~85 mV in WT mice to ~18 mV in heterozygous mice). This is consistent with the level of furosemide-induced reduction of the basilar membrane vibration [12] and threshold elevations in the tuning curves of auditory nerve fibers [13,14]. In homozygous mice, concurrent absence of intermediate cells and the EP further confirms the role of the intermediate cells in generating the EP [2,5,8].…”
Section: Discussionsupporting
confidence: 77%
“…Those studies demonstrated that, when K + concentration in the endolymph or the EP magnitude is reduced by locally or intravenously applied diuretic compounds such as furosemide [11], basilar membrane vibration is reduced at the characteristic frequency [12], and the threshold of tuning curves of auditory nerve fibers at the characteristic frequency is elevated [13,14]. Interestingly, while the electrochemical environment in the endolymph and the EP maintained by the stria has long been known to be important for hair cell mechanotransduction and cochlear amplification, it is unclear whether reduction or loss of the EP would affect hair cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this observation, furosemide reduces DPOAE amplitude and DPOAE threshold (Mills et al, 1993;Mills and Rubel, 1994;Mills and Schmiedt, 2004;Mills, 2003Mills, , 2006Rübsamen et al, 1995). Apart from reducing the receptor potential of both OHCs and IHCs, EP reduction hyperpolarises the resting membrane potential (Sewell, 1984b), which results in substantial reduction of the spontaneous activity and discharge rate of the auditory nerve fibres (Evans and Klinke, 1982;Sewell, 1984b,c) and, subsequently, in an elevation of neural threshold (Evans and Klinke, 1982;Sewell, 1984a;Rübsamen et al, 1995). These findings suggest that the loss of CAP threshold observed here, following furosemide application, is the consequence of concomitant alteration of the function of both the OHCs and the IHCs.…”
Section: Specificity Of the Edpt Estimator Of Cap Thresholdsupporting
confidence: 69%
“…There is no doubt that the almost two-octave gap between the 4 and 16 kHz bands could be resolved perceptually given the sharp frequency selectivity of cat basilar membrane (Cooper and Rhode, 1992), auditory nerve fiber (e.g., Kiang et al, 1965;Evans and Klinke, 1982), and AI neuron (Phillips and Irvine, 1981) responses, even at the stimulus levels used here. If the response suppression in AI was the product of an active habituation to the exposure Fig.…”
Section: Discussionmentioning
confidence: 96%